Antifungal Activity of Secondary Metabolites From Trichoderma sp. Against Fusarium Oxysporum f.sp. Cubense - Siswadi, Edi; Dinata, Gallyndra Fatkhu; Kusparwanti, Tri Rini; Pertami, Rindha Rentina Darah; Salim, Abdurrahman; Wulandari, Antika (P3M Politeknik Negeri Jember, 2025)
Fusarium oxysporum f.sp. cubense (Foc) is an important pathogenic fungus that causes Panama disease in banana. One approach to overcome this problem is to utilize secondary metabolites from Trichoderma sp. This research was conducted to determine the effect of administering secondary metabolites from Trichoderma sp. against pathogen Foc. These metabolites were applied at concentrations of 10%, 20%, and 30%, 40% alongside a fungicide active ingredient of phosphoric acid 400 SL. This study used a Completely Randomized Design with 6 treatments 4 repetition. The parameters observed included colony diameter and percentage of inhibitory. The extraction of secondary metabolite isolation could be obtained as much as 500 ml with reddish brown, thick and odorless characteristics. Secondary metabolites showed a significant effect in inhibiting the growth of the pathogen Foc. The results showed the 10% concentration proved to be the most effective to inhibit pathogen Foc, resulting in the smallest colony diameter of 0.58 cm and an in vitro inhibition rate of 90.73%.